8.-                    =               =           =9. _2x+1_ – __x2___+ _2x__   12x+8     6x+x-2 16x-8      m.c.m= 8 (3x+...
__x+1__ ax(a+x)           11.-                  m. c. m.
12.-                =13.-                +           -   =            +               -       = 1. (a+6)(a-4)       M.C. D...
15.-a3       + a+3       - a-1                 m.c.m: (a+1) ( a2-a+1)a3+1   a2-a+1        a+                  a3+1= (a+1) ...
a3+1
Upcoming SlideShare
Loading in...5
×

ejercicio 130 libro de baldor

12,934

Published on

0 Comments
7 Likes
Statistics
Notes
  • Be the first to comment

No Downloads
Views
Total Views
12,934
On Slideshare
0
From Embeds
0
Number of Embeds
0
Actions
Shares
0
Downloads
23
Comments
0
Likes
7
Embeds 0
No embeds

No notes for slide

ejercicio 130 libro de baldor

  1. 1. 8.- = = =9. _2x+1_ – __x2___+ _2x__ 12x+8 6x+x-2 16x-8 m.c.m= 8 (3x+2) (2x-1) 12x+8= 4(3x+2) 6x+x-2= (3x+2)(2x-1) 16x-8= 8(2x-1) = 2(2x+1)(2x-1) -8x2 + 2x (3x+2) 8 (3x+2) (2x-1) = 8x2 – 2 - 8x2 + 6x2 + 4x 8 (3x+2) (2x-1) = __6x2 + 4x – 2__ 8 (3x+2) (2x-1) =__2(3x2 +2x -1)_ =__3x2 + 2x – 1__ 8 (3x+2) (2x-1) 4 (3x+2) (2x-1)10. _1 - ____1____ + _1_ mcm=ax (a+x) ax a2 + ax a+x a+x-x+ax = _ax+a__ = _a(x+1)_ = ax(a+x) ax(a+x) ax(a+x)
  2. 2. __x+1__ ax(a+x) 11.- m. c. m.
  3. 3. 12.- =13.- + - = + - = 1. (a+6)(a-4) M.C. D. 2. (a-4)(a+2) = (a+2)(a-4)(a+6) 3. (a+6)(a+2) = =14.-xy=(x)(y)
  4. 4. 15.-a3 + a+3 - a-1 m.c.m: (a+1) ( a2-a+1)a3+1 a2-a+1 a+ a3+1= (a+1) ( a2-a+1) a2-a+1= NO HAY= a2-a+1 a+1=NO HAY= a+1 a3 + a+3 - a-1 = (a+1) ( a2-a+1) a3 + a2+4a+3 -(a3 -2a2 -2a-1) = (a+1) ( a2-a+1) a3 + a2+4a+3 -a3 +2a2 -2a + 1 = (a+1) ( a2-a+1) 3a2 + 2a +4 = (a+1) ( a2-a+1) R= 3a2 + 2a +4
  5. 5. a3+1

×